Career preferences of the Tinguian fourth year high school students and the implications to current local job opportunities - Bersalona, Carmelita B. 1948- (1977)
The main purpose of the study is to determine the career preferences of the Tinguian senior high school students. The factors which influence career choice, and the current local job opportunities. To obtain the necessary information to test the hypotheses of the study, quetionnaires and an inventory were administered. Interview schedule supplemented gathered data, which tabulated and statistically analyzed and tested for significant differences or relationships. Findings of the study suggest that male students had great interest in mechanical, computational and artistic activities which female students preferred musical and social activities. The factors which influence the Tinguian students' career choice were parents' advice, opportunity for employment, could best serve community, suitability to sex and friends' recommendation. Employment possibilities in a Mountain Tinguian locality is meager.
Appendices: leaves 92-138
Chiefly tables
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Occupations; Vocational interests; Abra -- Occupations